Mo, do, so, da – duortnussámi dovdomearkan? - Antonsen, Lene (Nordlyd, 2022)
In this article, I examine the dialect forms of a set of North Saami pronouns – mo, do, so, da (‘I, you, he/she, it’; standardized forms: mon, don, son, dan). More specifically, I investigate where the forms are in use and how the forms have developed. The material shows that the final -n has changed in a number of stages before it disappeared completely. I suggest that these pronominal forms are a dialect mark of the Torne Saami dialect group (named after the Torne river valley on the border between Sweden and Finland). The pronominal forms are used throughout this dialect area, and the use continues north to Kvænangen in Norway, which in turn belongs to the Sea Sami dialect group. In the Kvænangen dialect there are also a couple of other characteristics that are typical for some of the Torne Saami dialects. Artihkkalis guorahalan mo do so da pronomenhámiid: mo hámit leat gárggiidan, ja gos hámit leat geavahusas. Hámiid loahppa n lea jávkan cehkiid mielde. Evttohan mo do so da hámiid durdnossámi suopmanmearkan. Pronomenhámit geavahuvvojit durdnossámi golmma davimus váldosuopmanis, muhto davás gitta Návutnii, mii fas gullá mearrasámi suopmanjovkui. Návuona suopmanis leat maiddái moadde eará dovdomearkka mat leat mihtilmasat durdnosámi suopmaniidda.